Perceptions of the Solvency Assessment Management (SAM) framework by the South African insurance industry. - Mbugua, Peter Nelson (My University, 2016)
The SAM (Solvency Assessment and Management) framework to be implemented in South Africa in 2016 is a new risk-based approach to capital adequacy, risk governance and disclosure. The regulations replacing the current Financial Condition Reporting (FCR) initiative pose significant challenges to the insurance industry. The purpose of this study is to evaluate the perceptions of the Solvency Assessment and Management (SAM) regulatory framework impact on the capital structures and risk management measures in the South African short-term insurance industry. The study further explores the preparedness of insurers to meet the implementation date of 2016 and the consequent costs and challenges of the SAM implementation. A qualitative methodology was utilised for this study, with in-depth interviews and content analysis used to collect and analyse data. The study indicated similarities between the experiences of the SAM implementation and its counterpart in Europe, Solvency II, including increased capital requirements for insurers and improvement in risk management structures. The industry has also faced increased costs to meet the requirements of implementation and improving risk management, audit and actuarial functions. It is therefore imperative for the industry, and more importantly senior executives, to realise the new responsibilities on management of risk, governance and strategic decision-making. This study provides guidance to stakeholders so they can have a clearer perspective on the implications of the regulations and can prepare accordingly.
MBA
Keywords: Insurance companies -- South Africa. Insurance -- Mathematics. Risk management -- South Africa.